BIM Adoption in Construction Companies of Tehran Province, Using Technology Acceptance Model (TAM) - Sahar Taheripour; Mojtaba Azizi; Ehsanallah Eshtehardian (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Although in recent years, Building Information Modeling, as an emerging technology in the Iranian construction industry, has attracted the attention of many people, the low productivity of this industry and the conditions for the realization of many benefits from implementing this technology have faced many obstacles. Implementing such technologies on national, organizational, and individual scales depends on their adoption. According to previous research in this field, unfortunately, the adoption of BIM in Iran is very slow and undesirable.Methodology: The present study obtained the BIM adoption status using the Technology Acceptance Model (TAM) by distributing a questionnaire among the first-ranked construction companies in Tehran province.Findings: The data analysis using Structural Equation Modeling showed that BIM adoption was below average in all 87 valid samples. The research findings showed that if people imagine using BIM in their minds and beliefs more easily, they think it is useful. Both of these variables lead to a greater intention to adopt BIM technology.Originality/Value: The study indicates that improving the BIM adoption status in the Iranian construction industry may be possible by strengthening individual and behavioural dimensions to further BIM adoption.